ZOOPLANKTON COMMUNITY STRUCTURE AT AWUR BAY IN THE NORTHERN CENTRAL JAVA SEA - Muhammad Zainuri (JOURNAL OF COASTAL DEVELOPMENT, 1998)
Zooplankton abundance, diversity and community structure were estimated in the seagrass beds of Awur Bay, Jepara. The samples were collected during 36 hours observation in situ, from Nopember 1994 to April 1995 and covered a total 29 species, which holoplanoton, 7 meplankton and 6 nectobenthos. Result of Shannon Weaver Diversity Index and Cluster Analysis based on Bray Curtis values revealed patterns of zooplankton abundance, diversity and community structure. These are discussed with regard to sampling time and zooplankton life cycle. The zooplankton abundances range between 6800 – 22777 individuals/m3, with average 13698 individus/m3, while the diversity range between 2,48 – 2,86 and cumulatively 2,93. Zooplankton abundance and community structure fluctuated due to seasonal changes, during the first two months of the research, and increasing to a stable level in April 1995. This pattern of zooplankton community structure appears to be related to the ecological capacity and hydrodynamic. Keywords : zooplankton, seagrass, abundance, diversity, community structure, Awur Bay, Jepara.